Predicting Peak Wind Gusts During Specific Weather Types with the Meteorologically Stratified Gust Factor Model - (:unkn) unknown (My University, 2020)
Peak wind gusts were estimated by the meteorologically stratified gust factor model at Milwaukee, WI (KMKE) for eight different weather types during 2010-2017. The gust factor model couples gust factors with wind speed and direction forecast guidance to produce peak gust forecasts. The model evaluated used two model output statistics (MOS) guidance products at lags ranging from 6-24 hr and was compared with peak gust forecasts provided by the Localized Aviation MOS Program (LAMP) as well as observed gusts reported by automated surface observing systems (ASOS). Compared with climatology, the gust factor model showed skill when coupled with MOS in predicting peak gusts during most of the eight weather types at the analyzed lags of 06 hr, 12 hr, 18 hr, and 24 hr. The MOS products results performed similarly for each of the weather types. The gust factor model does not show skill during convective weather situations, in part because during these conditions the provided MOS wind speed and direction forecasts are less accurate. This is important for operational wind forecasting, because this method can be used for many non-convective gust-producing weather situations.
Keywords: gust factor model; Gust factors; gust forecasting; LAMP